Eksegesis Yohanes 2:4 - Sandrawati, Amellia Ardaning (Views : Jurnal Teologi dan Biblika, 2024)
Abstract: The purpose of this study is to identify and analyze the phrase "My hour has not yet come" uttered by Jesus in John 2:4 in a theological context. This phrase appeared when Jesus responded to Mary, his mother's request to help solve the problem that occurred at the wedding in Cana at that time, namely the lack of wine. This research uses a qualitative approach with a literature review to examine this phrase. In conclusion, from the research conducted by the researcher by paying attention to and analyzing the original text, and various historical and literary contexts, it can show that the phrase "my hour" refers to the moment of the revelation of Jesus' glory and part of the full realization of his divine mission. It also explores the eschatological and theological significance of the phrase, and gives its relevance for today. In addition, this study also discusses how this phrase is used in the gospel of John, which has or discusses the theme of salvation and redemption. Through this study, the researcher seeks to provide deeper insights into how divine time is understood and expressed in the context of Jesus' ministry life, as well as its relevance for Christian life today.